Selamento de lesões de cárie proximal com infiltrante resinoso: ensaio clínico randomizado - Correia, Rafaela Trevisan (2012)
The aim of this study was to evaluate the efficacy of an infiltrant (Icon, DMG, Germany) in molars and premolar´s lesions in patients attended to Dental Faculties in Santa Maria and Porto Alegre, each having two or more proximal lesions extending until the outer third of dentin. This was a split-mouth randomized doubleblind trial: the lesions were randomly allocated into two treatment groups; in the test group, lesions were infiltrated (Icon application) and the control group received a placebo treatment. All participants were assessed by visible plaque, papillary bleeding, salivary flow rate, dietary habits, DMFT. Fluoridation oral hygiene, dietary instructions and gel topical applications were given to all patients. After 12 months, radiographic lesion progression was evaluated using two different methods: (1) radiographs were read in pairs, (2) using subtraction radiography of digitized images. A total of 13 pairs of lesions finished the study. No difference in caries development was noted between the groups when read in pairs (p=1,0) and subtraction radiography (p=0,25). The baseline and final VPI were 24,13 ± 18,86 and 7,07 ± 4,45 (p=0,024) and the baseline and final SI were 18,38 ± 16,07 and 14,68 ± 2,62 (p=0,057). In conclusion, the use of a low viscosity resin on the treatment of proximal lesions is unnecessary when the patient adhere the non operative treatment of dental caries.